2012
DOI: 10.1557/jmr.2012.391
|View full text |Cite
|
Sign up to set email alerts
|

A novel and simple approach for characterizing the Young’s modulus of single particles in a soft matrix by nanoindentation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Furthermore it can be difficult to relate these measurements to models implemented in DEM. A few attempts have been made to measure the Young's modulus of single particles [22,23], the yield stress [24] and interfacial energy using atomic force microscopy [25,26]. A common approach is to choose the DEM input parameters by calibrating the DEM model against bulk global measurements and then to adjust these input parameters until the outputs match the experimental, usually macroscopic, observations [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it can be difficult to relate these measurements to models implemented in DEM. A few attempts have been made to measure the Young's modulus of single particles [22,23], the yield stress [24] and interfacial energy using atomic force microscopy [25,26]. A common approach is to choose the DEM input parameters by calibrating the DEM model against bulk global measurements and then to adjust these input parameters until the outputs match the experimental, usually macroscopic, observations [27].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been derived in order to characterize more complex materials such as composites. Kamlah et al [9] adapted extrapolation models used for thin films to particle-matrix composites. Ulm et al [10,11] used statistical deconvolution of indentation grids in order to extract properties of each phase.…”
Section: Introductionmentioning
confidence: 99%
“…In a particle-reinforced composite, nanoindentation on the particle could provide insight into the properties of the reinforcement [8][9][10][11][12][13]. Delincé et al [14] conducted nanoindentation tests on both ferrite and martensite phases of dual phase steels to determine their strengthening contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [9,10] found that the Oliver-Pharr method can still be used to measure the particle's Young's modulus with sufficient accuracy within a particle-dominated indentation depth. Leisen et al [13] used continuous stiffness measurement to reduce the amount of error caused by using the Oliver-Pharr method to measure the Young's modulus of a particle embedded in a soft matrix.…”
Section: Introductionmentioning
confidence: 99%